Controlling the input: How one‐year‐old infants sustain visual attention - Mendez, Andres H.; Yu, Chen; Smith, Linda B. (Developmental science, 2024)
Traditionally, the exogenous control of gaze by external saliencies and the endogenous control of gaze by knowledge and context have been viewed as competing systems, with late infancy seen as a period of strengthening top‐down control over the vagaries of the input. Here we found that one‐year‐old infants control sustained attention through head movements that increase the visibility of the attended object. Freely moving one‐year‐old infants (n = 45) wore head‐mounted eye trackers and head motion sensors while exploring sets of toys of the same physical size. The visual size of the objects, a well‐documented salience, varied naturally with the infant's moment‐to‐moment posture and head movements. Sustained attention to an object was characterized by the tight control of head movements that created and then stabilized a visual size advantage for the attended object for sustained attention. The findings show collaboration between exogenous and endogenous attentional systems and suggest new hypotheses about the development of sustained visual attention.